SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial - Karg, Margarete; Bosch, A.; Kannenkeril, Dennis; Striepe, Kristina; Ott, Christian; Schneider, M. P.; Boemke-Zelch, Franziska; Linz, Peter; Nagel, Armin Michael; Titze, Jens; Uder, Michael; Schmieder, Roland (Cardiovascular Diabetology, 2018)
Sodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.In a prospective double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to either dapagliflozin 10 mg or placebo once daily for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analysed the sodium content in the skin and muscles of the lower leg by Na-MRI.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11 mmHg, p = 0.010), and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024), 24-h ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline [24.1 ± 6.6 vs. 22.7 ± 6.4 A.U.(arbitrary unit) p = 0.013]. No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 A.U. p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in tissue sodium content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT02383238) retrospectively registered.
EVALuna2:4043